GLP-1 receptor agonists in IBD: exploring the crossroads of metabolism and inflammation - Migliorisi, Giulia; Gabbiadini, Roberto; Dal Buono, Arianna; Ferraris, Matteo; Privitera, Giuseppe; Petronio, Lorenzo; Bertoli, Peter; Bezzio, Cristina; Armuzzi, Alessandro (Frontiers in Immunology, 2025)
Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) represent a cornerstone in the treatment of diabetes and obesity and have emerged as a promising option for other metabolic disorders, including hepatic steatosis. Recent evidence highlights the direct and indirect anti-inflammatory properties of GLP-1, suggesting a potential additional therapeutic strategy for patients with inflammatory bowel disease (IBD). However, side effects of GLP-1 RAs, particularly those affecting the gastrointestinal system, may limit their use in patients with IBD. The rising prevalence of IBD worldwide and the ageing of the IBD population will likely increase the number of patients with metabolic comorbidities who may potentially benefit from a combination treatment with GLP-1 RAs. A profound comprehension of the physiological function of intestinal homeostasis and permeability is essential to more accurately evaluate the prospective application of GLP-1 RAs in patients with ongoing inflammation. While preclinical studies support this hypothesis, robust clinical evidence remains limited. This narrative review aims to provide a synthesis of current knowledge regarding the anti-inflammatory properties of GLP-1, with a particular focus on safety concerns and potential future directions for its use in IBD management.